Size and surface effects on transient photoconductivity in CdS nanobelts probed by time-resolved terahertz spectroscopy - Li, Mingjie (2013)
Ultrafast optical-pump terahertz probe spectroscopy was performed over a graduated size distribution of CdS nanobelts to investigate the size and surface effects on the transient photoconductivity. It was found that the nanobelt size has a profound influence on the carrier localization and photoconductivity dynamics, brought about by the carrier trapping at surface defects. The strong carrier localization in the nanobelt is ascribed to the internal surface boundaries arising from the surface depletion layer. The increased thickness of surface depletion layer due to a continuous trapping of photocarriers at surface defects results in more pronounced carrier localization after photoexcitation.